Students’ Problems in Listening Comprehension at Fourth Semester of English Education Study Program Peradaban University - Nurdiawati, Dede (LPPM Universitas Pancasakti Tegal, 2018)
The purpose of this study is to obtain descriptive information about the problems and problem solving in learning listening comprehension. The researcher uses descriptive qualitative research and investigates the students’ problems in listening comprehension at the fourth semester and the steps to overcome their problems. There are 23 students at the fourth semester of English Education Study Program Peradaban University in the academic year 2018/2019 as the sample. In collecting the data, the researcher uses questionnaire and interview as the instruments.The researcher finds the most problems faced by the fourth studentsare lack of concentration, native speaker speaking speed, unfamiliar words, and lack of effort to understand each word.The solution offeredto solve those problems are focus and concentrate while listening class, concentrate on what is heard, and write things that are important when listening to material spoken by native speaker; find the meanings of unfamiliar words, look at the dictionary to find out difficult words, check words that are not clearly heard in dictionary, memorize vocabulary, and read English text and listen to English audio; and familiarize the students with the rulers of pronunciation in order to help them hear the different forms of rapid natural speech and ask them to imitate native speakers’ pronunciation. It concludes that learning information about the problems and problem solving at the fourth semester are because of the fact that their learning outcomes are still far from being standard. Therefore, problem solving in listening comprehension learning is expected to minimize the problems faced by students of the fourth semester of English Education Study Program Peradaban University in learning process so that they get satisfying learning outcomes.